Real world digital photograph - Eismann, Katrin (Peachpit Press, 2004)
Whether you're just making the transition from a lifetime of traditional photography or are looking to bring your digital photography skills in line with today's market, if you're serious about digital photography, you need this book. In the four years since the first edition was published, just about every aspect of digital photography has changed (often radically--and it's all covered in these pages. Organized in four major sections--Digital Processing Essentials, Digital Processing Techniques, The Digital Darkroom, and Output and Presentation--the focus here is on getting great pictures and spectacular printed output through a combination of smart techniques and the right equipment. As with all of the titles in the Real World series, the authors here realize that this entails learning not just techniques but the concepts behind them. For a professional-level understanding of the digital photography process--from how a digital camera works to advice on buying cameras and accessories, choosing hardware and software, downloading and outputting images, and more--this is the place to turn.
Includes index. - Revised edition of: Real world digital photography / Deke McClelland, Katrin Eismann. c1999
Keywords: Digital cameras; Photography -- Digital techniques; Appareils photographiques numériques; Photographie numérique; Photography; Digital techniques; Visual Arts; Art, Architecture & Applied Arts; Photography